Bow-Tie Microstrip Antenna Design - Rahim, M. K. A.; Abdul Aziz, M. Z. A.; Goh, C. S. (2005)
In this paper, the bow-tie microstrip antennas have been designed with two different angles of 40Â° and 80Â°. An investigaton on the effect of the angle to the return loss and radiation patterns had been carried out. The impedance matching network with the niicrostrip transmission line feeding was used in this study. Simulation and measurement results for the return loss and radiation patterns were presented.